Archaean zircons in Miocene oceanic hotspot rocks establish ancient continental crust beneath Mauritius - Lewis D. Ashwal (Nature Portfolio, 2017)
There is growing evidence for the presence of continental fragments within the young oceanic basins, but this is still based on limited geological data. Here, the authors use zircon isotope geochronology to demonstrate the presence of Archaean continental crust beneath the young hotspot volcanoes of Mauritius.